Numerical Analysis of Forward-Facing Reverse-V Step Hull Angle on Resistance Characteristics of Planing Hull - Amam Baharullah; Sunarsih Sunarsih; Abdi Ismail (International Journal of Marine Engineering Innovation and Research, 2026)
This study investigates the hydrodynamic resistance characteristics of a forward-facing reverse-V stepped planing hull using a Computational Fluid Dynamics (CFD) approach under high-speed planing conditions. Five reverse-V angle configurations consisting of 180°, 165°, 150°, 135°, and 120° were evaluated at a constant speed of 27 knots (13.9 m/s) using the Reynolds-Averaged Navier–Stokes (RANS) and Volume of Fluid (VOF) methods. Unlike conventional aft-facing stepped hulls, the proposed reverse-V geometry redirects the flow inward toward the forward centerline region beneath the hull bottom, modifying pressure redistribution, cavity interaction, and wetted surface formation. The numerical simulations employed a Poly-Hexacore meshing strategy and demonstrated stable convergence behavior with excellent mesh-quality characteristics. The results show that the 165° and 150° configurations increased hydrodynamic resistance due to stronger turbulence interaction and larger wetted surface development around the step region. In contrast, sharper reverse-V configurations improved hydrodynamic performance through stronger inward pressure convergence and more compact cavity formation. The 120° configuration generated the lowest resistance value of 7463.052 N and achieved the highest resistance reduction of 2.02% compared to the baseline model.